The Role of Affective Sensemaking in the Constitution of Experience. The Affective Pertinentization Model (APER) - Salvatore, Sergio; De Luca Picione, Raffaele; Cozzolino, Mauro; Bochicchio, Vincenzo; Palmieri, Arianna (Integrative psychological & behavioral science, 2022)
The paper outlines a model of the basic cognitive process of the constitution of experience - the Affective Pertinentization Model (APER). The constitution of experience is intended as the basic cognitive process underpinning the meaning-maker’s experience of mental representations as self-contained, stable, substantive entities standing for something in the external reality. Framed within the general family of theories highlighting the embodiment of cognition, the APER model claims that affects are the basic mechanism at the basis of the constitution of human experience. The first part of the paper outlines the APER model; the second part reviews some preliminary evidence supporting it.